2021
DOI: 10.1111/hiv.13163
|View full text |Cite
|
Sign up to set email alerts
|

Improving healthcare for patients with HIV, tuberculosis and hepatitis C in eastern Europe: a review of current challenges and important next steps

Abstract: Objectives:In some eastern European countries, serious challenges exist to meet the HIV-, tuberculosis (TB)-and hepatitis-related target of the United Nations Sustainable Development Goals. Some of the highest incidence rates for HIV and the highest proportion of multi-drug-resistant (MDR) tuberculosis worldwide are found in the region. The purpose of this article is to review the challenges and important next steps to improve healthcare for people living with TB, HIV and hepatitis C (HCV) in eastern Europe.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…We found that the treatment success rate among cases with drug-susceptible and drug-resistant TB (61.4% and 34.6%, respectively) was low. Thirty-eight percent of new cases and 61% of previously treated cases were drug-resistant TB, which is consistent with other studies conducted in Eastern European region [ 11 15 ] but higher compared with other European regions [ 16 ]. The rate of previously treated cases for TB was high (30.7%) and the prevalence of relapse after treatment completion among them was also high.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that the treatment success rate among cases with drug-susceptible and drug-resistant TB (61.4% and 34.6%, respectively) was low. Thirty-eight percent of new cases and 61% of previously treated cases were drug-resistant TB, which is consistent with other studies conducted in Eastern European region [ 11 15 ] but higher compared with other European regions [ 16 ]. The rate of previously treated cases for TB was high (30.7%) and the prevalence of relapse after treatment completion among them was also high.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of miliary TB was 12.6% in new TB cases and 6.6% in previously treated TB cases and this form of TB was not associated with the poorer treatment outcome. In other large multicenter prospective studies [16,56], the rate of miliary TB was higher and the association with the increased risk of death was found. These differences could be explained by a larger number of participants and different stratifications used for analysis.…”
Section: Plos Onementioning
confidence: 77%
See 1 more Smart Citation
“…MDR-TB was defined as resistance of Mycobacterium tuberculosis (Mtb) for at least rifampicin, as done previously and reflecting WHO MDR-TB treatment guidelines [2,10]. If DST data was missing for some drugs and available for others, it was assumed that Mtb was susceptible to the missing drugs [9].…”
Section: Methodsmentioning
confidence: 99%
“…MDR-TB was defined as resistance of Mycobacterium tuberculosis (Mtb) for at least rifampicin, as done previously and reflecting WHO MDR-TB treatment guidelines [2,10]. If DST data was missing for some drugs and available for others, it was assumed that Mtb was susceptible to the missing drugs [9]. TB recurrence was defined as a new diagnosis of TB (either definite, probable or presumptive) after at least 6 months of consecutive treatment and at least 8 weeks of treatment interruption after the initial TB diagnosis in the TB:HIV study.…”
Section: Definitions and Proceduresmentioning
confidence: 99%